The Rage of Ivan Karamazov - POBRIĆ, Edin (Anafora, 2023)
The Brothers Karamazov novel by F. M. Dostoyevsky, with the questions he raises – the timothy of man – has lost nothing of its actuality. This paper is an attempt to bring closer to the contemporary man the topics with which the so-called primal questions are reduced to existential ones, metaphysics to ethics. Through his heroes, Dostoyevsky presents his thoughts on the history of man’s life on earth and his suffering, on freedom and faith, power and mystery, on authority and morality, and on man’s nature itself. Why is there evil in the world, why suffering exists? can a man, in general, love another man, can he love “without God,” is he able to “effectively love,”, and can Thanatos be eventually incorporated into Eros!? – are the questions that besiege Dostoyevsky’s heroes. In this novel, Dostoyevsky portrays the conflict of several worlds that is ultimately unsolvable by any system of binary oppositions.The individual principles of Ivan or Zosima, Christ or the Grand Inquisitor, Alyosha or Smerdyakov, with the worlds of all other characters, are read as one universe of opposites and, at the same time, some strange connections between all these worlds that do not seem to be wholly reasonably understood. Therefore, two opposing views at one same thing do not mean the stratification of reality here, but rather speaking of its essence, its apparent truth.